Impact of Sustainable Drainage with Porous Asphalt to Reduce Urban Flood Risk in Vulnerable Residential Areas - Meny Sriwati (Engineering Science Letter, 2026)
Climate change and rapid urbanization in Makassar have increased the frequency of heavy rainfall, causing excessive runoff and flooding in densely populated areas. Conventional drainage systems are no longer able to accommodate the increased water volume, thus creating an urgent need for sustainable engineering solutions. The objectives of this study were to test the effectiveness of porous asphalt in managing stormwater runoff and increasing infiltration, and to develop a sustainable drainage system model that suits the hydrological, technical, and socio-economic conditions of tropical urban areas. The method used was a quantitative experiment with a hydrological and environmental engineering approach. The study sample included twenty field test locations in flood-prone areas of Makassar. Data were collected through field infiltration measurements, SWMM simulations, and laboratory asphalt porosity tests. Analysis was performed using multiple linear regression and hydrological model validation. The results showed that porous asphalt was able to increase infiltration capacity from 210 to 340 mm/hour and reduce surface runoff volume by 40.7 percent. The inundation depth was reduced by half from the initial condition, and the drainage system efficiency increased from an index of 3.2 to 4.3. The correlation coefficient between porosity and infiltration reached 0.79 (p < 0.01), indicating a strong positive relationship. These findings indicate that the application of porous asphalt effectively reduces flood risk while improving environmental quality. In conclusion, porous asphalt is a feasible technical and ecological solution for water runoff management in tropical areas. Therefore, a sustainable drainage system based on porous asphalt can be a strategic component in adaptive urban development to climate change.